Intertemporal choice and income regularity: Non-fungibility in the timing of income among Kenyan farmers - Kramer, Berber; Kunst, David (Informa UK Limited, 2020)
The optimal design of informal contracts in agricultural value chains depends on when farmers prefer to be paid for their output. While the evidence from time preference experiments suggests a preference for early payments, field studies often indicate that farmers will defer regular payments if given the opportunity. In this study, we explicitly test whether farmers are more patient regarding regular, earned income than regarding experimental windfall payments. We asked farmers in a dairy cooperative in Kenya to allocate both their milk income and a one-time gift between an early and a deferred payment date. We find that a large majority of participants deferred their milk payments, while rarely choosing to defer the gift. Participants’ survey responses suggest that we observe this difference because of mental accounting: participants earmarked their regular milk payments, but not the gift, to save for bulky expenditures. We conclude that deferred payments can provide value to producers by functioning as a savings device, even when decisions over windfall income suggest a preference for early payments.